2020
DOI: 10.1063/5.0027861
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale compositional analysis of wurtzite BAlN thin film using atom probe tomography

Abstract: Note: This paper is part of the Special Topic on Ultrawide Bandgap Semiconductors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…2 Yao et al have utilized synchrotron x-ray topography to study the details of dislocations in AlN single crystals, 3 and a detailed study of vacancy defects in Si-doped Al 0.9 Ga 0.1 N using positron annihilation measurements is presented by Prozheev et al, where they determine that the charge state of the in-grown cation vacancy correlates with the carbon content. 4 The electrical properties of semi-polar (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Al x Ga 1Àx N films with x ¼ 0.6 and 0.8 are reported by Foronda et al, who found that the resistivity for both compositions is impacted by compensation due to the formation of cation vacancy complexes. 5 Kaminska et al conducted studies wherein PL and photoluminescence excitation (PLE) spectra determined that the bandgap of AlN depends on the growth substrate (Si or sapphire) due to lattice mismatch and the associated strain.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…2 Yao et al have utilized synchrotron x-ray topography to study the details of dislocations in AlN single crystals, 3 and a detailed study of vacancy defects in Si-doped Al 0.9 Ga 0.1 N using positron annihilation measurements is presented by Prozheev et al, where they determine that the charge state of the in-grown cation vacancy correlates with the carbon content. 4 The electrical properties of semi-polar (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Al x Ga 1Àx N films with x ¼ 0.6 and 0.8 are reported by Foronda et al, who found that the resistivity for both compositions is impacted by compensation due to the formation of cation vacancy complexes. 5 Kaminska et al conducted studies wherein PL and photoluminescence excitation (PLE) spectra determined that the bandgap of AlN depends on the growth substrate (Si or sapphire) due to lattice mismatch and the associated strain.…”
mentioning
confidence: 81%
“…For example, Tran et al have grown BAlN with over 20% B content by metalorganic chemical vapor deposition (MOCVD), 11 and the same group has conducted a nanoscale compositional analysis of similar films using atom probe tomography. 12 Additionally, Moser et al have studied the dielectric properties and phonon modes of ScAlN using infrared spectroscopic ellipsometry. 13 Moving to devices, a number of transistor results are likewise reported.…”
mentioning
confidence: 99%
“…[ 2,6–12 ] In addition, experimental efforts have been made toward understanding their crystal growth and structural properties. [ 7,8,11 ]…”
Section: Introductionmentioning
confidence: 99%
“…[2,[6][7][8][9][10][11][12] In addition, experimental efforts have been made toward understanding their crystal growth and structural properties. [7,8,11] Theory and simulations have been used to study the structure of a broader range of B-fractions of B x Al 1−x N alloys. Mainly two classes of methods have been used.…”
mentioning
confidence: 99%
See 1 more Smart Citation